Tectono-stratigraphic evolution of the northeastern sector of the Ñirihuau basin, north Patagonian Andes - Santonja, Camila (2019)
Fil: Santonja, Camila. Universidad de Buenos Aires, CONICET, Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires (IGEBA)